2013
DOI: 10.48550/arxiv.1311.2609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secular Evolution in Disk Galaxies

Abstract: Self-gravitating systems evolve toward the most tightly bound configuration that is reachable via the evolution processes that are available to them. They do this by spreading -the inner parts shrink while the outer parts expand -provided that some physical process efficiently transports energy or angular momentum outward. The reason is that self-gravitating systems have negative specific heats. As a result, the evolution of stars, star clusters, protostellar and protoplanetary disks, black hole accretion disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 210 publications
(296 reference statements)
1
10
0
Order By: Relevance
“…Sellwood 2013; Kormendy 2013, for up to date reviews). After the initial instability responsible for the bar formation, the bar itself generally undergoes a thickening that can be either caused by a second "buckling" instability or by a vertical resonance (Sellwood 2013), possibly responsible for the pseudobulge formation (Kormendy 2013). In this scenario, the gas could accrete with a more disk like dynamics until the bar thickens, and fall toward the MBH with a higher velocity dispersion after the pseudobulge forms if the buckling instability and/or any vertical resonances significantly affect the gas motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sellwood 2013; Kormendy 2013, for up to date reviews). After the initial instability responsible for the bar formation, the bar itself generally undergoes a thickening that can be either caused by a second "buckling" instability or by a vertical resonance (Sellwood 2013), possibly responsible for the pseudobulge formation (Kormendy 2013). In this scenario, the gas could accrete with a more disk like dynamics until the bar thickens, and fall toward the MBH with a higher velocity dispersion after the pseudobulge forms if the buckling instability and/or any vertical resonances significantly affect the gas motion.…”
Section: Discussionmentioning
confidence: 99%
“…The former are the result of major galactic mergers, which cause bursts of star formation (Daddi et al 2010;Genzel et al 2010), while the latter result from bar instabilities in galactic disks and undergo a slower, disk-like star formation (see, e.g. Kormendy 2013). In B12, both bar instabilities and major mergers were modeled, but star formation in the bulge component was the same irrespective of the bulge's formation mechanism.…”
Section: The Star Formation Modelmentioning
confidence: 99%
“…Bars are also thought to be responsible for the build-up of the pseudo/disky bulges, whose nearly exponential profiles hints to a disk origin (e.g. Kormendy 2013, for a review). These structures are the most common type of bulges among galaxies in the stellar-mass range 10 9.5 M⊙ < M * < 10 10.5 M⊙, while classical bulges dominate among more massive systems (e.g.…”
mentioning
confidence: 99%
“…On longer timescales, the removal of the gas forced towards nuclear regions affects the star formation processes within the bar extent (Cheung et al 2013;Fanali et al 2015), contributing to the lowering of the specific star formation rate in the most massive spiral galaxies at low redshift (Cheung et al 2013;Gavazzi et al 2015a). In addition to the effect of the bar onto the inter stellar medium (ISM), the dynamical evolution of the bar itself is advocated to be responsible for the boxy/peanut-shaped stellar bulges (B/P bulges hereafter) (see Kormendy 2013;Sellwood 2014, for a review), observed in ∼ > 40% of edge on disk galaxies (e.g. Lütticke, Dettman & Pohlan 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation